Economic Recovery in Response to Worldwide Crises: Fiduciary Responsibility and the Legislative Consultative Process with Respect to Bill 150 (Green Energy and Green Economy Act, 2009) and Bill 197 (COVID-19 Economic Recovery Act, 2020) in Ontario, Canada - Tsuji, Stephen R. J. (Western University, 2022)
The Green Energy and Green Economy Act (2009) was an omnibus bill that affected a number of other acts. Due to the breadth of its effects, it should have seen a rigorous consultation and review process; this is especially true given how it would impact First Nations and its explicit mention in the Bill. However, it took less than three months for it to receive Royal Assent and become an act. This timeline is extremely short, even among similar bills within the same context. One of the core reasons for this swift transition is due to its labeling as green energy, which has benign connotations. This effectively allowed the bill to be expedited through the consultation process. The consultation process had many hurdles of its own that inhibited meaningful consultation including its timeframe, location of hearings, accessibility, and other factors. The term green energy was also never defined within the Act, meaning it only served as a form of signaling. This raises many questions with respect to the Government of Ontario’s conduct in the situation and how they handled their legal duty to consult with Indigenous people of Ontario, Canada. There are many voices that have raised issues with this process. If nothing else, this example serves the purpose of demonstrating the dangers of green-labelling, especially to Indigenous people of Canada and other Indigenous groups worldwide.